2021
DOI: 10.33448/rsd-v10i4.14147
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos de diferentes técnicas extrativas na obtenção da β-ecdisona proveniente de Pfaffia glomerata: um estudo de revisão

Abstract: A Pfaffia glomerata é uma planta da família Amaranthaceae, presente naturalmente em inúmeras regiões brasileiras, com propriedades medicinais e usualmente empregada como anti estresse, para o aumento da imunidade e como afrodisíaco. Estas características se devem à presença da β-ecdisona, uma saponina presente exclusivamente nesta espécie e que possui grande valor comercial. Sendo assim, torna-se de interesse industrial e científico metodologias que otimizem a extração da β-ecdisona. Este trabalho objetivou re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Bertoco Júnior et al . (2021) subjected P. glomerata leaves and inflorescences to drying at 40 and 60 °C for 360 min and found no significant differences in colour parameters, in agreement with our results.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Bertoco Júnior et al . (2021) subjected P. glomerata leaves and inflorescences to drying at 40 and 60 °C for 360 min and found no significant differences in colour parameters, in agreement with our results.…”
Section: Resultssupporting
confidence: 88%
“…Similar findings were reported by Bertoco Júnior et al . (2021), who observed that higher drying temperatures led to a faster decrease in the moisture content of P. glomerata aerial parts (stems, leaves and inflorescences). In the cited study, the plant material took 180, 270 and 300 min to dry at 40, 60 and 80 °C respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The extraction is a unit operation that aims to separate the compounds from different matrices, solid or liquid, by chemical, physical, and/or mechanical methods [78]. The most critical factors in an extraction process are the type of solvent, the process conditions (temperature, pH, and the ratio between the solvent and the plant matrix), and the properties of the plant material (composition and particle size) [79]. The solvents used and their polarity can affect the transfer of electrons and hydrogen atoms, which is a critical aspect in the extraction of polyphenols and may affect the extraction yield and their antioxidant capacity [80].…”
Section: Extraction Methods Of Bioactive Compoundsmentioning
confidence: 99%